Noncytotoxic and antitumour-promoting activities of garcinia acid esters from Garcinia atroviridis Griff. ex T. Anders (Guttiferae) - Abd Manaf, Ali; Nashriyah, Mat (2012)
The in alio antitumour-promoting cytotoxic. and antioxidant activities of two ester denvahves of garcinia acid that is 2-(butoxycarbonylmethyl)-3- butoxycatbony1-2-hydroxy-3-propanoltde (1) and 1".1'-dibutyl methyl hydroxycarate (2) that had been previously isolated from the fruits of Garcinia atroviridis Grill ex T Anders (Guniferae) were examined Based on the inhibition of Epstein-Barr virus early antigen (EBV-EA) activation compound 1 (IC60 70M) showed much higher (84o/d)antitumour-promoting activity than compound 2 1050 560M) In addition both compounds were nontoxic towards CEM-SS (human Tlymphoblastic leukemia) cells (CNC 100M). Rap (human 13- lymphoblastoid) cells (CD60 600M) and brine shnmp (1060 300M) Ahhough the antitumour-promoting activity of compound 1 is moderate compared with the known antitumout promoter genistein. its non-toxicity suggests the potential of compound 1 and related structures as chernopreventhe agents. The weak antioxidant activity displayed by both compounds also suggested that the pnmary antitumour-promoting mechanism of compound 1 did not uwohe oxtdatne-stress quenching Copyright A 2012 fAukram M fAac keen et al